Genômica evolutiva de lontras (carnivora, mustelidae, lutrinae) - Ferran, Vera de (2021)
The use of genomic approaches is revolutionizing several areas of Biology, including evolutionary, ecological and biogeographic studies, along with their application on the conservation and management of endangered species. In spite of their great potential, these tools are still not broadly applied to the majority of the world’s biodiversity, and their use can accelerate the resolution of old problems as well as reveal additional levels of complexity in previously described patterns. In this thesis, I have applied genomic methods to characterize the evolutionary history of otters (Mammalia: Carnivora: Mustelidae: Lutrinae), including different approaches to investigate a set of relevant problems in this field. The thesis comprises a General Introduction, followed by three data chapters formatted as scientific manuscripts, which address the following topics: (i) phylogenomics of the 13 currently recognized species of extant otters, using complete genomes and including molecular dating analyses, reconstruction of demographic history and characterization of present-day genomic diversity; (ii) phylogeography of Lontra longicaudis using genome-wide markers (Ultraconserved Elements [UCEs]), which indicated that this species is not monophyletic; and (iii) identification and characterization of molecular markers (microsatellite loci) in the genomes of 11 otter species, generating sets that are recommended for genetic and ecological studies targeting these organisms. The thesis also includes a chapter on perspectives for future studies in this area, based on the results presented here, and two appendices describing additional research activities performed during the Ph.D. program, focusing on natural populations of the giant otter (Pteronura brasiliensis). Overall, the studies contained herein have contributed to resolve several questions, among which the following can be highlighted: (i) phylogenetic relationships and divergence time estimates among all the currently recognized otter species; (ii) support with nuclear data for the recognition of the African otter Aonyx congicus as a distinct species; (iii) comparative reconstruction of demographic history for otters from different continents; (iv) estimates of genomic diversity for extant otters, and comparison to their conservation status; and (v) indication that L. longicaudis must be subdivided into two distinct species, with trans-Andean populations being recognized as L. annectens. Therefore, I hope that the results obtained in these studies contribute to the advancement of this field, as well as provide useful data that can be incorporated in conservation efforts focusing on these organisms.